Effects of fine‐scale forest habitat quality on movement and settling decisions in juvenile pond‐breeding salamanders. Issue 7 (1st October 2014) - Osbourn, Michael S.; Connette, Grant M.; Semlitsch, Raymond D.
Abstract : A better understanding of how individuals respond to variation in habitat quality while moving through heterogeneous habitats is needed to predict ecological phenomena at larger scales, such as local population and metapopulation dynamics. We sought to identify how fine‐scale habitat quality affects the decisions of juvenile pond‐breeding salamanders ( Ambystoma maculatum and A. annulatum ) to cease dispersive movements away from their natal pond, select a refuge, and settle. Because of the acute susceptibility of juvenile amphibians to evaporative water loss in terrestrial habitats, we predicted that they possess mechanisms for adjusting their behavior in response to variations in fine‐scale habitat quality. We used experimental field enclosures to isolate the effects of habitat quality on settling behavior and employed generalized linear mixed models to examine how manipulations in canopy cover (closed or open) and microhabitat (control, compacted soils, high coarse woody debris, high burrow density), along with environmental variables (rainfall and air temperature), affect the individual's probability of settling. Our results indicated that A. maculatum and A. annulatum had a 10% and 30% decreased probability of settling in open‐canopy clearcut habitat, respectively, compared to closed‐canopy forest habitat. In addition, A. annulatum were 24% less likely to settle in compacted soil treatments. Although the settlement probability of A. annulatum did not depend on refuge availability, A. maculatum were 18% and 25% more likely to settle under conditions of high burrow density and high coarse woody debris, respectively. These findings make a unique contribution to our understanding of amphibian movement ecology by demonstrating how the interplay of external factors and individual behavior produce observed patterns of movement and habitat selection.